2022
DOI: 10.3390/en15114101
|View full text |Cite
|
Sign up to set email alerts
|

Development of Sustainable Biorefinery Processes Applying Deep Eutectic Solvents to Agrofood Wastes

Abstract: The growing demand for renewable energies and the application of sustainable and economically viable biorefinery processes have increased the study and application of lignocellulosic biomass. However, due to lignocellulosic biomass recalcitrance hindering its efficient utilization, the pretreatment in the biorefinery is an essential stage for success in the process. Therefore, Deep Eutectic Solvent (DES) has emerged as a promising green pretreatment. During this study, the effect of choline chloride [ChCl]:gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The reported result showed 80 and 15% acid-soluble lignin and Klason lignin isolation, respectively. In addition, it showed increment of saccharification yields with 60, 80, and 100% of dextran, xylan, and arabinoxylan, respectively [96].…”
Section: Type Of Biomassmentioning
confidence: 90%
See 1 more Smart Citation
“…The reported result showed 80 and 15% acid-soluble lignin and Klason lignin isolation, respectively. In addition, it showed increment of saccharification yields with 60, 80, and 100% of dextran, xylan, and arabinoxylan, respectively [96].…”
Section: Type Of Biomassmentioning
confidence: 90%
“…In the study, wheat straw pretreatment was conducted by utilizing chloride: lactic acid (1:2) and DES solution (1:20 solid-to-liquid ratio) at various temperatures (90, 120, 150, and 180°C) for 6 and 12 h. It is reported that the yields of lignin were increased from 15.26 to 81.54% and purity of 91.33% with temperature increase from 90 to 180°C. Thus, the optimal temperature obtained in the pretreatment of wheat straw for lignin isolation was 150°C for 6 h [96]. Lou et al conducted a comprehensive analysis of lignin nanoparticle synthesis from wheat straw using ChCl: LA-based DES.…”
Section: Reaction Temperaturementioning
confidence: 99%